88.3k views
3 votes
Solve for x in the following equation 3(6+8x)=3(6x+1)

2 Answers

2 votes
The answer is x = -2 and 5/6. The picture will tell you why and how.
Solve for x in the following equation 3(6+8x)=3(6x+1)-example-1
User Arzar
by
4.7k points
2 votes

first divide the two sides of the equation by 3 to make it simpler:


(3)/(3) (6+8x)= (3)/(3) (6x+1)


6 + 8x= 6x+1

substract the two sides from 6x + 1:


6 + 8x - (6x + 1)= 6x+1 - (6x + 1)


6 + 8x - 6x - 1= 6x+1 - 6x - 1


5 + 2x = 0

substract the two sides from 5:


2x = - 5

divide by 2:


x = - (5)/(2)

User Arseniy Zhizhelev
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.